Antigone between the living and the dead: exiles and spectres in María Zambrano (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This article aims to analyzing and projecting María Zambrano's representation of Antigone’s myth within contemporary debates about the recovery of the bodies of human victims in post-violence contexts. Beyond the mythic-religious framework in which The Tomb of Antigone seems to be located, it will be unraveled the different semantic and philosophical layers underlying Zambrano's re-reading of the Theban heroine. This will pave the way towards highlighting the subversive political potential of Antigone's gesture by embracing historical subjects traditionally marginalized from the public space.
Keywords: Antigone; María Zambrano; mourning; victims; exile